A key to the Mexican genera of Tanymecini (Coleoptera: Curculionidae) - Cortés-Hernández, Kevin A.; Morrone, Juan J. (Zootaxa, 2019)
We provide a key to the eight genera of the tribe Tanymecini distributed in Mexico. Habitus photographs of all genera are included as are photographs of various other key characters. A brief synopsis of each genus is included as well as a list of the species recorded for Mexico. The species Minyomerus languidus Horn and Pandeleteius championi Howden are newly recorded for Mexico.